A Cross-Sectional Assessment of Knowledge Attitude and Practice of Breast Self-Examination among Female Undergraduates Pharmacy Students in Two Nigeria Universities - Onyinye, Ukoha-kalu Blessing; Abdulmuminu, Isah; Onyine, Aluh Deborah (International Journal of Scientific Research in Biological Sciences, 2019)
Breast Self Examination (BSE) is an uncomplicated/noninvasive and cost effective technique that enables women master their breast contour and makes it easy for early detection of any abnormality.The objective of this study was to compare the Knowledge, Attitude and Practice of Breast Self examination among female pharmacy students in two tertiary institutions in south eastern Nigeria.A cross sectional survey of pharmacy students of UNN and UNIZIK was conducted using an already validated questionnaire. SPSS version 16 was used for analysis of data. Descriptive (frequencies, percentages) and inferential (independent t-test, Chi-square and Mann Whitney tests) statistical analysis performed on the data. A p-value of less than 0.05 was considered significant. About 451 and 163 students of UNN and UNIZIK responded to the questionnaire respectively, of which 61% and 58.9% had good knowledge, 52.8% and 51.5% had good attitude, 59.6% and 56.4% had good practice of Breast self examination respectively. The study revealed that students had good Knowledge, Attitude and Practice of Breast self examination. UNN students had a better knowledge when compared to students from UNIZIK. The major source of Breast self examination information was from health care professionals.